Healthcare costs and resource utilization associated with treatment of out-of-hospital cardiac arrest. (August 2020) - Geri, Guillaume; Scales, Damon C.; Koh, Maria; Wijeysundera, Harindra C.; Lin, Steve; Feldman, Michael; Cheskes, Sheldon; Dorian, Paul; Isaranuwatchai, Wanrudee; Morrison, Laurie J.; Ko, Dennis T.
Abstract: Background: The management of out-of-hospital cardiac arrest (OHCA) patients requires the coordination of prehospital, in-hospital and post-discharge teams. Data reporting a comprehensive analysis of all costs associated with treating OHCA are scarce. We aimed to describe the total costs (and their components) related to the management of OHCA patients. Patient and methods: We performed an analysis on a merged database of the Toronto Regional RescuNet Epistry database (prehospital data) and administrative population-based databases in Ontario. All non-traumatic OHCA patients over 18 years of age treated by the EMS between January 1, 2006, and March 31, 2014, were included in this study. The primary outcome was per patient longitudinal cumulative healthcare costs, from time of collapse to a maximum follow-up until death or 30 days after the event. We included all available cost sectors, from the perspective of the health system payer. We used multivariable generalized linear models with a logarithmic link and a gamma distribution to determine predictors of healthcare costs. Results: 25, 826/44, 637 patients were treated by EMS services for an OHCA (mostly male 64.4%, mean age 70.1). 11, 727 (45%) were pronounced dead on scene, 8359 (32%) died in the emergency department, 3640 (14%) were admitted to hospital but died before day-30, and 2100 (8.1%) were still alive at day-30. Total cost was $690 [interquartile range (IQR) $308, $1742] per patient; ranging from $290 [IQR $188, $390] for patients who were pronounced on scene to $39, 216 [IQR 21, 802, 62, 093] for patients who were still alive at day-30. In-hospital costs accounted for 93% of total costs. After adjustment for age and gender, rate of patient survival was the main driver of total costs: the rate ratio was 3.88 (95% confidence interval 3.80, 3.95), 49.46 and 148.89 for patients who died in the ED, patients who died after the ED but within 30 days, and patients who were still alive at day-30 compared to patients who were pronounced dead on scene, respectively. Factors independently associated with costs were the number of prehospital teams (rate ratio (RR) 5.50 [5.32, 5.67] for being treated by 4 teams vs. 1), the need for hospital transfer (RR 2.38 [2.01, 2.82]), coronary angiography (RR 1.43 [1.27, 1.62]) and targeted temperature management (RR 1.25 [1.09, 1.44]). Conclusion: Survival is the main driver of total costs of treating OHCA patients in a large Canadian health system. Inpatient costs accounted for the majority of the total costs; potentially modifiable factors include the number of prehospital teams that arrive to the scene of the arrest and the need for between-hospital transfers after successful resuscitation.